Things that disappear - Erpenbeck, Jenny, 1967- (New Directions paperbook, 2025)
"'Things that disappear' is an exciting collection of interlinked miniature prose pieces that grapple with the phenomenon of disappearance, from everyday objects like socks, to close friends and the social norms of common courtesy, to East German sites like the Palace of the Republic or the Berlin sightlines now blocked by the new construction. Erpenbeck asks, 'Is there a perpetrator who makes things that I know and cherish disappear?' These things disappear, and yet do they really? Do they remain in our memories more fully than if they continued to exist? Beautifully translated by Kurt Beals, 'Things that disappear' offers a window into the Booker Prize-winning writer's sense of the past and of her own self as a writer"--Page 4 of cover.